Metode Latihan Terbimbing dan Tanya Jawab pada Pembelajaran Hybrid: Upaya Membantu Pemahaman Konsep Matematis Siswa SMP - Halawa, Agnes Monica; Dirgantoro, Kurnia Putri Sepdikasari (Program Studi Pendidikan Matematika, 2023)
Understanding mathematical concepts is an important element in the mathematics learning process that plays a fundamental role in achieving quality learning outcomes. However, in the context of hybrid learning, it was found that students' understanding of mathematical concepts was still lacking. Therefore, this study aims to apply guided exercise and question and answer methods as a solution to overcome these problems. This learning method was chosen because it has proven effective in hybrid learning environments, where the role of the teacher is very significant in the delivery of material. The purpose of this study is to illustrate how the application of guided practice and question and answer methods in hybrid learning can contribute to improving students' understanding of mathematical concepts. The research method used is a descriptive qualitative approach. The results showed that the application of guided practice and question and answer methods was able to make a positive contribution to students' understanding of mathematical concepts, by involving active participation of all students in the learning process. As a recommendation, teachers need to continue to evaluate and develop this method in order to achieve more optimal results in mathematics learning.